2021
DOI: 10.1371/journal.pone.0246803
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of inhalable composite niclosamide-lysozyme particles: A broad-spectrum, patient-adaptable treatment for coronavirus infections and sequalae

Abstract: Niclosamide (NIC) has demonstrated promising in vitro antiviral efficacy against SARS-CoV-2, the causative agent of the COVID-19 pandemic. Though NIC is already FDA-approved, administration of the currently available oral formulation results in systemic drug levels that are too low for the inhibition of SARS-CoV-2. We hypothesized that the co-formulation of NIC with an endogenous protein, human lysozyme (hLYS), could enable the direct aerosol delivery of the drug to the respiratory tract as an alternative to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…A phase I clinical study of niclosamide has reported peak plasma concentrations ranging from 35.7-182 ng/ml (109-556 nM) 75 , which encompasses the IC 50 value of 0.13 μM reported here. Niclosamide is known to have limited resorption efficacy, which might be enhanced by improving the niclosamide formulation or by developing an inhalable derivate for local application 76 . Both MK-2206 and niclosamide might be promising candidates for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I clinical study of niclosamide has reported peak plasma concentrations ranging from 35.7-182 ng/ml (109-556 nM) 75 , which encompasses the IC 50 value of 0.13 μM reported here. Niclosamide is known to have limited resorption efficacy, which might be enhanced by improving the niclosamide formulation or by developing an inhalable derivate for local application 76 . Both MK-2206 and niclosamide might be promising candidates for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, direct delivery of niclosamide to the lung could overcome the limitations of oral administration and achieve high drug concentration at the site of infection, i.e., the lungs. Brunaugh et al [ 76 ] engineered composite particles containing niclosamide and an endogenous protein, human lysozyme, for inhalation delivery to the lungs. This study demonstrated that the co-formulation of niclosamide with lysozyme is four-fold more potent against coronaviruses compared to niclosamide alone.…”
Section: Inhaled Covid-19 Therapeuticsmentioning
confidence: 99%
“…Similarly, niclosamide has shown promising in vitro antiviral efficacy against SARS-CoV-2 [276] . A potential immunomodulatory response has also been observed, involving an up-regulation in IL-1β activity and decreased expression of IL-6, TNF-α [277] . However, in its oral dosage form, systemic drug levels are too low to inhibit SARS-CoV-2.…”
Section: Drug Delivery Strategies For Immune Modulation In Infectious Diseasementioning
confidence: 99%